Doing gender locally: The importance of ‘place’ in understanding marginalised masculinities and young men’s transitions to ‘safe’ and successful futures - Michael Ward (The Sociological Review, 2017)
Anxieties have been developing about the position of boys and young men in contemporary society in recent years. One explanation for this apparent ‘crisis’ is the supposed lack of father figures and male role models, which is thought to have negative impacts on their successful transitions into adulthood. Drawing on research conducted with young people who accessed a range of social care support services, this paper argues that transition means different things for young men in different locales and that local definitions of masculinity are more significant for understanding young men’s lives. We argue that home life, street life, individual neighbourhoods, regions and nations all shaped the young men’s identities and the particular practices they (and the staff working with them) drew on in order to create successful futures and ‘safe’ forms of masculinity. We suggest that this place based approach has potential to re-shape the ‘crisis’ discourse surrounding masculinity and the anxieties associated with young men.